2020
DOI: 10.3390/ijerph17197164
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Norm Perception on Pro-Environmental Behavior: A Comparison between the Moderating Roles of Traditional Media and Social Media

Abstract: The activation of norm perception can promote pro-environmental behavior. How does media, as important variables in activating norm perception, affect pro-environmental behavior? Through an online survey of 550 randomly selected Chinese citizens, this study examines the roles of traditional media and social media in influencing the relationship between norm perception and pro-environmental behavior. Based on multi-level regression analysis of data, this study found that (1) compared with traditional media, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 36 publications
5
33
0
Order By: Relevance
“…When individuals have high dependency and attention toward the information on SNSs, their fear of victimization increases and their pro-environmental behaviors are positively and significantly influenced. Similarly, previous research suggests that SNSs play an important role in regulating the the normative perceptions and pro-environmental behaviors of individuals [8]. However, Ho, Liao, and Rosenthal [135] demonstrated that media and Internet attention significantly moderate the media's influences on the pro-environmental and engagement behaviors of people.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…When individuals have high dependency and attention toward the information on SNSs, their fear of victimization increases and their pro-environmental behaviors are positively and significantly influenced. Similarly, previous research suggests that SNSs play an important role in regulating the the normative perceptions and pro-environmental behaviors of individuals [8]. However, Ho, Liao, and Rosenthal [135] demonstrated that media and Internet attention significantly moderate the media's influences on the pro-environmental and engagement behaviors of people.…”
Section: Discussionmentioning
confidence: 82%
“…Nevertheless, media (mass media and social networking sites (SNSs)) play a critical role in providing environmental education, increasing people’s knowledge, and shaping the societal perception of climate change and its effect on society [ 2 , 3 , 4 , 5 , 6 ]. SNSs reach a large number of people, attract user attention toward environmental problems, raise awareness, and provide information about the adverse impacts of climate change on civil society [ 7 , 8 ]. SNSs can significantly influence individual and collective ecological concerns, environmental attitudes, and users’ pro-environmental behaviors [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of newspaper and radio exposure are inconclusive; these media may reduce or increase fatalistic cancer beliefs [ 62 , 63 ]. Frequent Internet use has not been found to significantly influence or reduce the belief that cancer is fatal [ 64 ].…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Since television and print media exposure enhances fatalistic beliefs while Internet exposure diminishes them [ 68 ], social media may also reduce cancer fatalism perceptions. Furthermore, social media differ from mass media in that they tend to involve interpersonal communication with local, more personally relevant information [ 64 , 70 ], which is positively associated with lower risk perceptions and a better knowledge of cancer [ 71 , 72 ].…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…In the past, various factors have been considered that affect PEB such as personal norms, attitudes, intentions, value orientations, environmental concerns, self-identity, etc. [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Psychological empowerment can also play an essential role in improving ecological behaviours, as it empowers an individual with the feeling of “the power to change things” and motivates consumers to preserve the environment [ 18 ].…”
Section: Introductionmentioning
confidence: 99%